Quick scripture reference for counseling women - Miller, Patricia A. (Grand Rapids, Mich. Baker Books, 2002)
This concise, topical resource of Scripture references covers approximately ninety topics that today's women face, including abortion, aging/menopause, bitterness, career, co-dependency, divorce, empty nest, flirtation, hospitality, marriage, past memor
Keywords: Women -- Pastoral counseling of. Church work with women. Christian women -- Religious life